Glicogenose hereditária em bovinos Brahman no Brasil : Inherited glycogenosis in Brahman cattle in Brazil - Zlotowski, P. (2005)
An inherited disease of cattle, characterized by lysosomal storage of glycogen in several tissues, is reported. The disease was diagnosed in a Brahman herd in the municipality of Porto Lucena, Rio Grande do Sul, Brazil. Affected calves, after one month of age, showed progressive difficulty to follow their mother, retarded growth, muscular weakness and tremors, lethargy and poor body condition. All affected calves were sired by the same bull. Necropsy was performed on three affected calves. The only gross lesion detected was paleness of the skeletal muscles of the trunk and limbs. Cytoplasmic vacuoles, the main histological lesion, were particularly evident in skeletal muscles, myocardium and Purkinje fibers, in neurons of the brain and spinal cord. Large amounts of periodic acid Schiff (PAS) positive granules were also observed in these most severely affected tissues. Pretreatment with diastase completely abolished the PAS reactivity. The 1057?TA, a lethal mutation in the gene of the acid alpha-glucosidase, which causes generalized glycogenosis in Brahman cattle, was detected by PCR in paraffin embedded tissues of affected animals on which post-mortem examination was performed. Clinical, histological and molecular findings were similar to previous descriptions of generalized glycogenosis in Brahman cattle in Australia. No previous indexed reports about generalized glycogenosis of Brahman cattle in Brazil could be found.